25 Years of Dividend Policy Research in Indonesia (1998-2023): A Bibliometric Perspective - Faldesiani, Riske; Ciptagustia, Annisa; Purnomo, Budi Supriatono; Purnamasari, Imas; Firmansyah, Egi Arvian (Image : Jurnal Riset Manajemen, 2024)
This study presents a comprehensive bibliometric analysis of dividend policy literature spanning the past twenty-five years (1998–2023), with a specific focus on Indonesia. Employing advanced computational mapping techniques using Biblioshiny and VOS Viewer, the research analyses 948 relevant Scopus-indexed articles and seminar papers. Key search terms included “dividend policy,” “dividend payout ratio,” and “dividend puzzle.” Articles specifically addressing "Indonesia" were mapped and scrutinized to uncover trends and insights. The findings offer a nuanced perspective on the evolution of dividend policy research, shedding light on its application in Indonesia's financial management landscape and providing a robust foundation for future scholarly inquiries.